Planning and task performance in a second language (Language learning and language teaching, 2005)
The last decade has seen a growing body of research investigating various aspects of L2 learners' performance of tasks. This book focuses on one task implementation variable: planning. It considers theories of how opportunities to plan a task affect performance and tests claims derived from these theories in a series of empirical studies. The book examines different types of planning (i.e. task rehearsal, pre-task planning and within-task planning), addressing both what learners do when they plan and the effects of the different types of planning on L2 production. The choice of planning as th